Evaluating User Experience of the Workout Tracker Feature in the FIT HUB Mobile Fitness Application Using the User Experience Questionnaire and Usability Testing - Khansa Sulthanah Rumi; Agustin Rusiana Sari (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The rapid development of digital fitness applications in Indonesia has been driven by increasing public awareness of healthy lifestyles. FIT HUB is a digital fitness application that provides a Workout Tracker feature to help users record and monitor their exercise activities. However, user reviews indicate that several issues remain, particularly related to feature clarity, navigation, and system stability. This study aims to evaluate the user experience of the FIT HUB application and identify areas for improvement to enhance user satisfaction and sustained application usage. This study employs a mixed-method approach by combining the User Experience Questionnaire (UEQ) and usability testing methods. Data were collected through the distribution of UEQ questionnaires to application users and the implementation of usability testing to identify usability issues encountered during task completion. The analysis results were used as a reference for formulating interface design improvement recommendations. The results of the UEQ evaluation indicate that the FIT HUB application demonstrates strong performance in terms of attractiveness and stimulation. However, aspects related to efficiency and novelty still require improvement. Furthermore, usability testing revealed several obstacles, particularly in accessing video tutorial features and storing exercise data. Based on these findings, an improved interface prototype was designed with a focus on enhancing feature clarity, navigation usability, and motivational elements. This study concludes that the combination of UEQ and usability testing methods is effective in identifying user experience issues and generating relevant interface design improvement recommendations for digital fitness applications